BiNi nano-alloy particle loaded carbon material as well as preparation method and application thereof

By uniformly loading BiNi nanoalloy particles on the sheet graphite carbon, using a combination of hydrothermal method and high-temperature calcination method, the problem of excessive adsorption energy of nickel-based electrode materials in the two electron oxygen reduction reaction is solved, and efficient preparation is achieved The properties of hydrogen peroxide and simplify the synthesis route.

CN119465255AActive Publication Date: 2025-02-18TIANJIN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411621179.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The existing nickel-based electrode materials have too strong adsorption energy in the two-electron oxygen reduction reaction, which leads to the occurrence of the four-electron oxygen reduction reaction path and the complication route, which hinders its practical application.

Method used

The combination of hydrothermal method and high-temperature calcination method is used to regulate the size of BiNi alloy particles and the formation of carbon skeleton to achieve uniform loading of BiNi nano alloy particles on the sheet graphite carbon.

Benefits of technology

The selectivity and activity of hydrogen peroxide preparation in the two electron oxygen reduction reaction is improved, the synthesis route is simplified, the material cost is reduced, and the material stability is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465255A_ABST
    Figure CN119465255A_ABST
Patent Text Reader

Abstract

The invention discloses a BiNi nano-alloy particle loaded carbon material, which is characterized in that BiNi nano-alloy particles are uniformly loaded on lamellar graphite carbon, and the strength ratio of a D band to a G band of the lamellar graphite carbon is about 0.94; the particle size of the BiNi nano alloy particles ranges from 2.0 nm to 20.0 nm. The invention further discloses a preparation method and application of the BiNi nano-alloy particle loaded carbon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to a BiNi nano alloy particle-loaded carbon material, a preparation method and use thereof. Background Art

[0002] As a green oxidant, hydrogen peroxide has a wide range of applications in chemical synthesis, disinfection, wastewater treatment and other fields. Compared with the traditional anthraquinone method for preparing hydrogen peroxide, the two-electron oxygen reduction reaction method has attracted much attention due to its advantages such as environmental protection and energy saving. However, there is competition between the two-electron oxygen reduction reaction and the four-electron oxygen reduction reaction, resulting in low selectivity and yield of hydrogen peroxide. In theory, the selectivity of the oxygen reduction reaction is highly dependent on the adsorption energy and adsorption mode of the *OOH intermediate on the active site. When the *OOH intermediate is adsorbed on the surface of the material in a "side-on configuration", the adsorption energy of *OOH is too strong, resulting in the breakage of the OO bond and inducing the four-electron oxygen reduction reaction path; if the adsorption mode of *OOH is "end-on adsorption", the adsorption energy is moderate, which is conducive to the occurrence of the two-electron oxygen reduction reaction. Therefore, it is of great significance to develop electrode materials with adjustable electronic structures to adjust the adsorption properties of *OOH and the pathway of oxygen reduction reaction.

[0003] In recent years, nickel-based electrode materials have been widely used in the field of two-electron oxygen reduction reactions; however, unmodified or improperly modified nickel-based materials have poor two-electron oxygen reduction reaction activity and selectivity. Most nickel-based materials have the problem of too strong adsorption energy of the *OOH intermediate, which makes it easy to undergo a four-electron oxygen reduction reaction. In order to improve the selectivity of the two-electron oxygen reduction reaction, various strategies such as crystal form regulation, vacancy engineering, and single atom engineering have been adopted to regulate the electronic structure of nickel-based materials. ACS Catalysis 2022, 12, 5911-5920 reported that the *OOH intermediate prefers to be adsorbed on amorphous NiO in an "end-to-end mode". x The two-electron oxygen reduction reaction process was effectively promoted by the Ni cation vacancy (V) through the cation engineering strategy. Ni ) is introduced into nickel phosphide (Ni 2-x PV Ni ) material, V NiThe induced geometric and electronic structure optimization makes the *OOH adsorption model an "end-to-end configuration". Although the above methods have made substantial progress, the electronic structure of Ni is still difficult to achieve precise regulation, and the activity and stability of the obtained Ni-based electrical materials are still limited; in addition, the synthesis routes of these nickel-based electrical materials are cumbersome, which hinders their practical application. Alloying is an effective strategy for synthesizing high-performance two-electron oxygen reduction reaction electrode materials. For alloy electrode materials, active metal sites can be separated by another metal, thereby extending the distance or spacing of the active metal sites, thereby promoting the occurrence of the "end-to-end adsorption" configuration of *OOH. So far, precious metal alloys such as palladium-mercury, silver-mercury and platinum-mercury are efficient electrode materials for the preparation of hydrogen peroxide (see Advanced Science 2021,8,2100076). These precious metal alloy materials have the advantages of small overpotential and high hydrogen peroxide selectivity, and the inherent inertness of precious metal alloys can ensure the durability of the materials in practical applications. However, these precious metal alloy materials have the disadvantages of high cost, scarcity and toxicity, which seriously hinder their practical application; in addition, some metals in the precious metal alloy materials, such as mercury, can only serve as inactive sites to isolate active metal sites (palladium, platinum, silver), resulting in low atomic utilization of precious metal alloy materials. Alloying highly active Ni metal with other non-precious metals for electrode materials may be an ideal strategy to enhance the two-electron oxygen reduction reaction to prepare hydrogen peroxide. For this reason, the present invention is proposed. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a BiNi nano alloy particle-loaded carbon material and a preparation method thereof. The present invention adopts a method combining a hydrothermal method and a high-temperature calcination method for the first time, and realizes the regulation of the BiNi alloy particle size by regulating the proportion of the metal source in the hydrothermal reaction process; the alloy particle growth and the formation of the carbon skeleton are achieved by high-temperature calcination, and finally the BiNi alloy nano particles are uniformly loaded on the surface of the lamellar graphite carbon. The material of the present invention is used to prepare a hydrogen peroxide electrode material and has excellent performance in preparing hydrogen peroxide by two-electron oxygen reduction.

[0005] The technical solution of the present invention is as follows:

[0006] The first aspect of the present invention discloses a BiNi nano alloy particle-loaded carbon material, wherein BiNi nano alloy particles are uniformly loaded on lamellar graphite carbon, the intensity ratio of the D band to the G band of the lamellar graphite carbon is about 0.94; the particle size of the BiNi nano alloy particles is 2.0-20.0nm.

[0007] Preferably, the molar ratio of Bi to Ni in the BiNi alloy is 0.125.

[0008] The second aspect of the present invention discloses a method for preparing the BiNi nano alloy particle-loaded carbon material, comprising the following steps:

[0009] (1) Preparation of Bi / Ni-MOF: dissolving terephthalic acid in a mixed solution of N,N-dimethylformamide, anhydrous ethanol and deionized water, and ultrasonicating for a period of time; then, adding bismuth salt and nickel salt with a certain molar ratio, and ultrasonicating for a period of time to obtain a mixed solution; hydrothermally reacting the mixed solution at a certain temperature for a period of time, separating, washing and drying to obtain Bi / Ni-MOF;

[0010] (2) BiNi nano alloy particle loaded carbon material: The Bi / Ni-MOF prepared in step (1) is placed in a nitrogen atmosphere and calcined at high temperature for a period of time, and then cooled to room temperature to obtain the BiNi nano alloy particle loaded carbon material.

[0011] Preferably, in step (1), the bismuth salt is bismuth nitrate pentahydrate, and the nickel salt is nickel chloride hexahydrate; the molar ratio of bismuth nitrate pentahydrate to nickel chloride hexahydrate is 0.100-2.000.

[0012] Preferably, in step (1), the ultrasonic time is 5-30 minutes; the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 12-20 hours; and the washing is performed by washing with deionized water and anhydrous ethanol for no less than three times respectively.

[0013] Preferably, the heating rate of high-temperature calcination in step (2) is 5°C / min, the calcination temperature is 600-800°C, and the calcination time is 2-6 hours.

[0014] The third aspect of the present invention discloses the use of the BiNi nano alloy particles loaded with carbon material as electrode material.

[0015] Preferably, BiNi nano alloy particles loaded with carbon material are used to prepare hydrogen peroxide electrode material.

[0016] Beneficial effects of the present invention:

[0017] 1. The BiNi nano alloy particle-loaded carbon material of the present invention is a BiNi nano alloy particle uniformly loaded on lamellar graphite carbon, the intensity ratio of the D band to the G band of the lamellar graphite carbon is about 0.94; the particle size of the BiNi nano alloy particle is 2.0-20.0nm. The BiNi nano alloy particle-loaded carbon material of the present invention is used for preparing an electrode material for hydrogen peroxide. When the molar ratio of Bi to Ni is 0.125, the obtained BiNi nano alloy particle has the most excellent performance of preparing hydrogen peroxide by two-electron oxygen reduction. When the molar ratio of Bi to Ni is 0.125, in addition to forming BiNi nano alloy particles with a ratio of Bi to Ni atoms of 1:1, there is also the presence of Ni metal element; at this time, Bi in the BiNi nano alloy particle acts as an isolation site, realizing the physical isolation and electronic isolation of the Ni site, greatly reducing the electron cloud density of the Ni site, thereby facilitating the occurrence of the "end-to-end adsorption" mode of the *OOH intermediate, thereby improving the selectivity and activity of preparing hydrogen peroxide by two-electron oxygen reduction reaction. In addition, precious metal alloy materials often have only one metal as an active site, and the atomic utilization rate is low. However, the material of the present invention can maximize the utilization of atoms due to the special electronic structure of BiNi alloy. Compared with the highly active nickel-based electrical materials reported in the prior art, the material of the present invention has excellent performance.

[0018] 2. The preparation method of the material of the present invention first obtains Bi / Ni-MOF (Metal Organic Framework), realizes the growth of alloy nanoparticles and the formation of graphite carbon skeleton by high temperature calcination, and finally obtains BiNi alloy nanoparticles uniformly loaded on the surface of lamellar graphite carbon material. The preparation method of the present invention has the advantages of simple synthesis route, controllable size of BiNi alloy nanoparticles, and reasonable optimization of Ni electronic structure, which is conducive to improving the industrial application value and potential of the preparation method. The preparation method of the present invention solves the problems of high cost, scarcity and high toxicity of precious metal alloy electrode materials to a certain extent.

[0019] 3. The BiNi nano alloy particles of the present invention are loaded on a carbon material. The microstructure diagram when the molar ratio of Bi to Ni in the BiNi alloy is 0.125 is shown in FIG. Figure 8 As shown, in Figure 8In the present invention, the BiNi nano alloy particles and part of the metal Ni particles are uniformly dispersed and immobilized on the surface of the carbon material or in the pores of the carbon material. The metal-based materials alone often have the problem of poor stability, which is caused by the serious leaching of metal ions during the electrocatalytic process. The BiNi nano alloy particles in the present invention are immobilized on the lamellar graphite carbon skeleton, and the protection of the carbon material improves the stability of the BiNi nano alloy particles to a certain extent. In addition, the lamellar graphite carbon material of the present invention has a rich pore structure as a carrier, which is conducive to the exposure of active sites and accelerates the mass transfer process. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a flow chart of the preparation method of the BiNi nano alloy particle loaded carbon material of the present invention.

[0021] Figure 2 These are SEM images of BiNi nano-alloy particles loaded with carbon materials prepared in Examples 1-6, which are respectively SEM images of BiNi / C-2 (a), BiNi / C-1 (b), BiNi / C-0.5 (c), BiNi / C-0.375 (d), BiNi / C-0.25 (e), and BiNi / C-0.125 (f).

[0022] Figure 3 These are the XRD diagrams of BiNi / C-2, BiNi / C-1, BiNi / C-0.5, BiNi / C-0.375, BiNi / C-0.25, and BiNi / C-0.125 obtained in Examples 1-6.

[0023] Figure 4 This is the SEM image of Bi / Ni-MOF-0.125 prepared in step 1 of Example 6.

[0024] Figure 5 These are the TEM image (a), high-magnification TEM image (b), element distribution map (c), particle size statistical distribution map (d), and linear scanning spectrum (e) and (f) of BiNi / C-0.125 prepared in Example 6.

[0025] Figure 6 This is the Raman image of BiNi / C-0.125 prepared in Example 6.

[0026] Figure 7 This is the XRD pattern of the material obtained in Example 7.

[0027] Figure 8 It is a schematic diagram of the microstructure of the BiNi nano alloy particle loaded carbon material (BiNi / C-0.125) of Example 6.

[0028] Fig. 9These are the performance diagrams of preparing hydrogen peroxide by two-electron oxygen reduction reaction of BiNi nano-alloy particles loaded with carbon materials of Examples 1-6; they are: (a) linear sweep voltammogram, (b) selectivity of hydrogen peroxide (H2O2%), and (c) number of electron transfers (n) of the reaction. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with specific implementation methods. It should be noted that the following examples are only used to illustrate and explain the present invention in detail, and the application scope of the present invention is not limited by the conditions in the examples.

[0030] Example 1: Figure 1 The process described above includes the following steps for preparing BiNi nano alloy particle-loaded carbon material (BiNi / C-2):

[0031] Step 1, preparation of Bi / Ni-MOF-2: 0.25 g of terephthalic acid was dissolved in a mixed solution of 64 mL of N,N-dimethylformamide, 4 mL of anhydrous ethanol and 4 mL of deionized water, and ultrasonicated for 15 min; then, bismuth nitrate pentahydrate and nickel chloride hexahydrate (1 mmol of bismuth nitrate pentahydrate and 0.5 mmol of nickel chloride hexahydrate) with a molar ratio of 2 were added, and ultrasonicated for 15 min; the mixed solution was transferred to a 100 mL stainless steel reactor containing a polytetrafluoroethylene liner, and hydrothermally reacted at 160° C. for 12 h; after the reaction was completed, the solid was filtered, and the solid was fully washed three times with deionized water and anhydrous ethanol respectively, and dried at 60° C. to obtain Bi / Ni-MOF-2;

[0032] Step 2, preparation of BiNi alloy-supported carbon material (BiNi / C-2): The Bi / Ni-MOF prepared in step 1 is placed in a tubular furnace in a nitrogen atmosphere for high-temperature calcination at a temperature of 675°C, a calcination time of 2h, and a heating rate of 5°C / min; after cooling to room temperature, the obtained BiNi nano alloy particle-supported carbon material (BiNi / C-2) has a morphology and structure as shown in FIG. Figure 2 As shown in a.

[0033] Example 2: Preparation of BiNi nano alloy particles loaded with carbon material (BiNi / C-1).

[0034] Step 1, preparation of Bi / Ni-MOF-1: 0.25g of terephthalic acid was dissolved in a mixed solution of 64mL of N,N-dimethylformamide, 4mL of anhydrous ethanol and 4mL of deionized water, and ultrasonicated for 15min. Then, bismuth nitrate pentahydrate and nickel chloride hexahydrate (0.75mmol of bismuth nitrate pentahydrate and 0.75mmol of nickel chloride hexahydrate) with a molar ratio of 1 were added, and ultrasonicated for 15min; the mixed solution was transferred to a 100mL stainless steel reactor containing a polytetrafluoroethylene liner, and hydrothermally reacted at 160℃ for 12h; after the reaction, the solid was filtered, and the solid was fully washed three times with deionized water and anhydrous ethanol respectively, and dried at 60℃ to obtain Bi / Ni-MOF-;

[0035] Step 2 is the same as in Example 1: the obtained BiNi nano alloy particles loaded with carbon material (BiNi / C-1) have a morphology and structure as shown in FIG. Figure 2 As shown in b;

[0036] Example 3: Preparation of BiNi nano alloy particles loaded with carbon material (BiNi / C-0.5).

[0037] Step 1, preparation of Bi / Ni-MOF-0.5: 0.25g of terephthalic acid was dissolved in a mixed solution of 64mL of N,N-dimethylformamide, 4mL of anhydrous ethanol and 4mL of deionized water, and ultrasonicated for 15min. Then, bismuth nitrate pentahydrate and nickel chloride hexahydrate (0.5mmol of bismuth nitrate pentahydrate and 1mmol of nickel chloride hexahydrate) with a molar ratio of 0.5 were added, and ultrasonicated for 15min; the mixed solution was transferred to a 100mL stainless steel reactor containing a polytetrafluoroethylene liner, and hydrothermally reacted at 160℃ for 12h; after the reaction, the solid was filtered, and the solid was fully washed three times with deionized water and anhydrous ethanol respectively, and dried at 60℃ to obtain Bi / Ni-MOF-0.5;

[0038] Step 2 is the same as in Example 1: the obtained BiNi nano alloy particles loaded with carbon material (BiNi / C-0.5) have a morphology and structure as shown in Figure 2 As shown in c.

[0039] Example 4: Preparation of BiNi nano alloy particles loaded with carbon material (BiNi / C-0.375).

[0040] Step 1, preparation of Bi / Ni-MOF-0.375. Dissolve 0.25g of terephthalic acid in a mixed solution of 64mL of N,N-dimethylformamide, 4mL of anhydrous ethanol and 4mL of deionized water, and ultrasonicate for 15min; then, add bismuth nitrate pentahydrate and nickel chloride hexahydrate (0.409mmol of bismuth nitrate pentahydrate and 1.091mmol of nickel chloride hexahydrate) with a molar ratio of 0.375, and ultrasonicate for 15min; transfer the mixed solution to a 100mL stainless steel reactor containing a polytetrafluoroethylene liner, and hydrothermally react at 160°C for 12h; after the reaction, filter, wash the solid three times with deionized water and anhydrous ethanol respectively, and dry at 60°C to obtain Bi / Ni-MOF-0.375;

[0041] Step 2 is the same as in Example 1: the obtained BiNi nano alloy particles loaded with carbon material (BiNi / C-0.375) have a morphology and structure as shown in FIG. Figure 2 As shown in d.

[0042] Example 5: Preparation of BiNi nano alloy particles loaded with carbon material (BiNi / C-0.25)

[0043] Step 1, preparation of Bi / Ni-MOF-0.25: 0.25g of terephthalic acid was dissolved in a mixed solution of 64mL of N,N-dimethylformamide, 4mL of anhydrous ethanol and 4mL of deionized water, and ultrasonicated for 15min. Then, bismuth nitrate pentahydrate and nickel chloride hexahydrate (0.3mmol of bismuth nitrate pentahydrate and 1.2mmol of nickel chloride hexahydrate) with a molar ratio of 0.25 were added, and ultrasonicated for 15min; the mixed solution was transferred to a 100mL stainless steel reactor containing a polytetrafluoroethylene liner, and hydrothermally reacted at 160℃ for 12h; after the reaction, the solid was filtered, and the solid was fully washed three times with deionized water and anhydrous ethanol respectively, and dried at 60℃ to obtain Bi / Ni-MOF-0.25;

[0044] Step 2 is the same as in Example 1: the obtained BiNi nano alloy particles loaded with carbon material (BiNi / C-0.25) have a morphology and structure as shown in Figure 2 As shown in e.

[0045] Example 6: Preparation of BiNi nano alloy particles loaded with carbon material (BiNi / C-0.125)

[0046] Step 1: Preparation of Bi / Ni-MOF-0.125: 0.25 g of terephthalic acid was dissolved in a mixed solution of 64 mL of N,N-dimethylformamide, 4 mL of anhydrous ethanol and 4 mL of deionized water, and ultrasonicated for 15 min; then, bismuth nitrate pentahydrate and nickel chloride hexahydrate (0.167 mmol bismuth nitrate pentahydrate and 1.333 mmol nickel chloride hexahydrate) with a molar ratio of 0.125 were added, and ultrasonicated for 15 min; the mixed solution was transferred to a 100 mL stainless steel reactor containing a polytetrafluoroethylene liner, and hydrothermally reacted at 160 ° C for 12 h; after the reaction, the solid was filtered, and the solid was fully washed three times with deionized water and anhydrous ethanol respectively, and dried at 60 ° C to obtain Bi / Ni-MOF-0.125, whose morphology and structure are as follows Figure 4 As shown;

[0047] Step 2 is the same as in Example 1: the obtained BiNi nano alloy particles loaded with carbon material (BiNi / C-0.125) have a morphology and structure as shown in FIG. Figure 2 f.

[0048] Example 7: Preparation of BiNi nano alloy particles loaded with carbon material (BiNi / C-0.1)

[0049] Step 1: Preparation of Bi / Ni-MOF-0.1: Dissolve 0.25g of terephthalic acid in a mixed solution of 64mL N,N-dimethylformamide, 4mL of anhydrous ethanol and 4mL of deionized water, and ultrasonicate for 15min. Then, add bismuth nitrate pentahydrate and nickel chloride hexahydrate (0.136mmol bismuth nitrate pentahydrate and 1.364mmol nickel chloride hexahydrate) with a molar ratio of 0.1, and ultrasonicate for 15min; transfer the above mixed solution to a 100mL stainless steel reactor with a polytetrafluoroethylene liner, and hydrothermally react at 160℃ for 12h; after the reaction, filter, and wash the solid three times with deionized water and anhydrous ethanol respectively; dry at 60℃ to obtain Bi / Ni-MOF-0.1;

[0050] Step 2 is the same as in Example 1: The XRD pattern of the obtained material is as follows Figure 7 As shown, from Figure 7 It can be seen that the obtained material is Ni / NiO / C material, not BiNi nano alloy particle-loaded carbon material. Therefore, when the BiNi molar ratio is less than 0.1, BiNi nano alloy particle-loaded carbon material cannot be obtained.

[0051] Figure 2 1 is a SEM image of the BiNi nano alloy particles loaded with carbon material obtained in Examples 1-6. It can be seen from the figure that as the molar ratio of bismuth nitrate pentahydrate to nickel chloride hexahydrate decreases, the size of the obtained alloy particles gradually decreases; and when the molar ratio is 0.125, the size of the obtained BiNi alloy particles is the smallest and most uniform ( Figure 2 f). Therefore, the size of the alloy particles can be regulated by regulating the molar ratio of the metal sources in step 1. However, when the molar ratio of Bi to Ni is less than 0.1, BiNi nano alloy particles cannot be obtained.

[0052] Figure 3 The left figure is the XRD diagram of the BiNi nano alloy particle-loaded carbon material obtained in Example 1-5. Figure 3 The right figure is the XRD pattern of the BiNi nano alloy supported carbon material obtained in Example 6. As shown in the figure, all materials are at 25.2°(400), 30.3°(224), 33.4°(008), 42.3°(-228), 44.4°(040), 54.7°(444), 56.6°(048), 57.8°(116), 63.0°(448), 73.0°(-264), 75.8°(-4412), 76.4°(1008) places and observe obvious characteristic peaks, which belong to BiNi alloy, indicating the successful synthesis of BiNi alloy. In addition, as the molar ratio of pentahydrate bismuth nitrate and hexahydrate nickel chloride decreases, the prepared material also gradually appears characteristic peaks belonging to metallic nickel at 44.5°(111) and 51.8°(200).

[0053] Figure 4 This is a SEM image of Bi / Ni-MOF-0.125 prepared in step 1 of Example 6. It can be seen that Bi / Ni-MOF-0.125 is a micron-scale flower-like structure assembled by layers. Figure 2 It can be seen from Figure 5 that the BiNi / C-0.125 obtained after high-temperature calcination can still maintain the morphology and structure of Bi / Ni-MOF-0.125, indicating that the structure of the material has strong stability.

[0054] Figure 5 The following are the TEM images (a), high magnification TEM images (b), element distribution images (c), particle size statistical distribution images (d), and linear scanning spectra (e) and (f) of BiNi / C-0.125 prepared in Example 6. Figure 5 a shows that the metal nanoparticles are uniformly loaded on the carbon skeleton. From the particle size statistical distribution diagram ( Figure 5 d) It can be seen that the average size of metal particles in the statistical range of 8-14 nanometers is 10.8 nanometers; some metal particles with sizes smaller or larger than this range are not included in the statistical chart. Figure 5 b It can be seen that the spacing of the lattice fringes is about 0.267 nm, which belongs to the (002) crystal plane of BiNi, which further indicates the successful preparation of BiNi alloy. Figure 5 c is the element distribution diagram of BiNi alloy, Figure 5c It can be seen that Bi, Ni and O elements are evenly distributed on the metal particles, and C elements are evenly distributed around the metal particles; this shows that the BiNi alloy is successfully immobilized on the surface of the carbon material, and the BiNi alloy is slightly oxidized. Figure 5 f is Figure 5 From the line scan spectrum of the metal particles in e, it can be seen that the signal intensities of Bi and Ni are comparable, which further verifies the successful synthesis of BiNi alloy.

[0055] Figure 6 This is the Raman image of BiNi / C-0.125 prepared in Example 6. As can be seen from the figure, 94 cm -1 The characteristic peak at belongs to Bi-Ni; the properties of graphite carbon can be reflected by the intensity ratio of D band to G band, and the ratio of the intensity ratio of D band to G band is relatively large, about 0.94; this indicates that the carbon material of BiNi / C-0.125 has a rich defect structure; the analysis results of Raman test further confirmed the microstructure of BiNi / C-0.125, that is, BiNi nano-alloy particles are loaded on the surface of carbon material.

[0056] Figure 7 This is the XRD diagram of the material prepared in Example 7; wherein, the peaks at 37.2°(111), 43.3°(200), 62.9°(220), and 75.4°(311) belong to the characteristic peaks of NiO; the peaks at 44.5°(111) and 51.9°(200) belong to the characteristic peaks of Ni; indicating that the main components of the obtained material are Ni and NiO. It can be seen that as the molar ratio of bismuth nitrate pentahydrate to nickel chloride hexahydrate further decreases, when the molar ratio of Bi to Ni is less than 0.1, no BiNi alloy is produced in the obtained material; this may be due to the fact that the amount of the metal bismuth source added is too small.

[0057] Figure 8 It is a schematic diagram of the microstructure of the BiNi nano alloy particle-loaded carbon electric material (BiNi / C-0.125) of the present invention; Figure 8 is based on Figure 3 and Figure 5 The microstructure diagram is drawn based on the analysis results. At this time, the BiNi nano alloy particles and some metal nickel particles are evenly dispersed and immobilized on the surface of the carbon material or in the pores of the carbon material.

[0058] Example 8: Performance evaluation of the BiNi nano alloy particles loaded with carbon materials of Examples 1-6 for preparing hydrogen peroxide electrode materials.

[0059] The performance of preparing hydrogen peroxide by the two-electron oxygen reduction reaction of the BiNi nano-alloy particles loaded on carbon materials prepared in Examples 1-6 was evaluated by a standard three-electrode system using a rotating ring disk electrode. In the three-electrode system, the counter electrode was a platinum mesh, the reference electrode was an Ag / AgCl electrode, and the rotating ring disk electrode of the BiNi nano-alloy particles loaded on carbon materials in Examples 1-6 was the working electrode: 5.0 mg of the BiNi nano-alloy particles loaded on carbon materials in Examples 1-6 were dispersed in 1.0 mL of a mixed solution containing 800 uL of isopropanol, 170 uL of deionized water, and 30 uL of Nafion solution (5 wt%), and ultrasonically treated for at least 1 hour to form a uniform suspension; 5 uL of the suspension was dropped on the disk surface of the rotating ring disk electrode; before the electrochemical test, the carbon material was charged at 100 mV·s in a 0.1 M KOH electrolyte saturated with N2. -1 Cyclic voltammetry (40 cycles) was performed at a scan rate of 1.5 % to activate the electrode surface; all potentials were relative to the standard hydrogen electrode (RHE): E RHE =E Ag / AgCl +0.197+0.059×pH; tested at a rotating ring disk electrode at 1600 rpm in an O2-saturated 0.1M KOH electrolyte with a scan rate of 5 mV·s -1 , the ring potential was set to 1.4 V vs. RHE. The selectivity of hydrogen peroxide (H2O2%) and the number of electron transfer (n) were calculated by the following formulas:

[0060]

[0061]

[0062] The performance of the two-electron oxygen reduction reaction of the BiNi nano alloy particles loaded with carbon materials in Examples 1-6 to prepare hydrogen peroxide is as follows: Fig. 9 As shown; Fig. 9 a is the linear sweep voltammogram, Fig. 9 It can be seen that with the decrease of the molar ratio of bismuth nitrate pentahydrate and nickel chloride hexahydrate, the starting potential of the obtained material gradually increases, and the disk current and ring current also gradually increase; among them, the starting potential of BiNi / C-0.125 is 0.76V vs.RHE, with larger disk current and ring current, indicating its excellent two-electron oxygen reduction reaction performance. Fig. 9 b and 9c are the selectivity of hydrogen peroxide (H2O2%) and the number of electron transfers (n) of the reaction, respectively. Fig. 9 b It can be seen that within the wide potential window range of 0.2-0.6 V, BiNi / C-0.125 has the highest hydrogen peroxide selectivity, up to 98%; Figure 8c shows that the electron transfer number of BiNi / C-0.125 is closest to 2; this indicates that BiNi / C-0.125 has the best performance in preparing hydrogen peroxide by two-electron oxygen reduction; while BiNi / C-2, BiNi / C-1, BiNi / C-0.5, BiNi / C-0.375 and BiNi / C-0.25 have poor performance in producing hydrogen peroxide by two-electron oxygen reduction. The reasons may be as follows: First, the size of BiNi alloy particles is large (100nm-20um) and uneven, resulting in low exposure of metal active sites; second, larger BiNi alloy particles cannot be stably immobilized on the surface of carbon materials, resulting in reduced stability; third, the accumulation of a large number of larger BiNi alloy particles results in a lower specific surface area of ​​the material, making it difficult for reactants to reach the active sites; fourth, with the increase of the molar ratio of bismuth nitrate pentahydrate to nickel chloride hexahydrate, the conductivity of the resulting material gradually decreases, hindering the electron transfer process.

[0063] It can be seen from the above embodiments that the preparation method proposed in the present invention can well realize the preparation of BiNi nano-alloy particles loaded on carbon materials, and nano-scale non-precious metal alloy particles loaded on lamellar graphite carbon materials can be prepared by changing the ratio of metal sources; among them, the electron transfer number for preparing hydrogen peroxide by the two-electron oxygen reduction reaction of BiNi / C-0.125 nano-alloy particles loaded on carbon materials is closest to 2, and the hydrogen peroxide selectivity is the highest, up to 98%.

[0064] The above description is only used to introduce the specific implementation methods of the present invention in detail, but the technical solution proposed by the present invention is not limited to the above method. Without departing from the basic principles of the present technology, equivalent modifications and changes made by those skilled in the art to the technology proposed by the present invention should be included in the scope of the claims of the present invention.

Claims

1. A BiNi nano alloy particle loaded carbon material, characterized in that: The BiNi nano alloy particles are uniformly loaded on lamellar graphite carbon, the intensity ratio of the D band to the G band of the lamellar graphite carbon is about 0.94; and the particle size of the BiNi nano alloy particles is 2.0-20.0 nm.

2. The BiNi nano alloy particle-loaded carbon material according to claim 1, characterized in that: The molar ratio of Bi to Ni in the BiNi alloy is 0.

125.

3. The method for preparing the BiNi nano alloy particle-loaded carbon material according to any one of claims 1-2, characterized in that: The steps include: (1) Preparation of Bi / Ni-MOF: dissolving terephthalic acid in a mixed solution of N,N-dimethylformamide, anhydrous ethanol and deionized water, and ultrasonicating for a period of time; then, adding bismuth salt and nickel salt with a certain molar ratio, and ultrasonicating for a period of time to obtain a mixed solution; hydrothermally reacting the mixed solution at a certain temperature for a period of time, separating, washing and drying to obtain Bi / Ni-MOF; (2) BiNi nano alloy particle loaded carbon material: The Bi / Ni-MOF prepared in step (1) is placed in a nitrogen atmosphere and calcined at high temperature for a period of time, and then cooled to room temperature to obtain the BiNi nano alloy particle loaded carbon material.

4. The preparation method according to claim 3, characterized in that: In step (1), the bismuth salt is bismuth nitrate pentahydrate, and the nickel salt is nickel chloride hexahydrate; the molar ratio of bismuth nitrate pentahydrate to nickel chloride hexahydrate is 0.100-2.

000.

5. The preparation method according to claim 3, characterized in that: In step (1), the ultrasonic time is 5-30 minutes; the temperature of the hydrothermal reaction is 160-200° C., and the time of the hydrothermal reaction is 12-20 hours; and the washing is performed by washing with deionized water and anhydrous ethanol for no less than three times respectively.

6. The preparation method according to claim 3, characterized in that: In step (2), the heating rate of high temperature calcination is 5°C / min, the calcination temperature is 600-800°C, and the calcination time is 2-6 hours.

7. Use of the BiNi nano alloy particles loaded with carbon material as electrode material according to any one of claims 1-2.

8. The use according to claim 7, characterized in that The invention discloses a method for preparing a hydrogen peroxide electrode material by using BiNi nano alloy particles loaded with carbon materials.

Citation Information

Patent Citations

  • Metal Bi nano-particle loaded Ni-MOF composite material as well as preparation method and application thereof

    CN117364156A